LEGAL IMPLICATIONS OF LIMITATIONS OF HEALTH FINANCING IN ENSURING ACCESS TO BASIC HEALTH SERVICES - Erdi Effendi Nasution; Marice Simarmata (PT. Radja Intercontinental Publishing, 2025)
This research examines the legal implications of limited health financing in ensuring access to basic health services in Indonesia. It analyzes the legal provisions governing health financing and explores the challenges posed by limited funding in realizing the constitutional right to health for all citizens. The study reviews relevant legislation, including the Constitution, Human Rights Law, and the Health Law, alongside various health insurance schemes. The findings highlight the state's responsibility to provide equitable and just health services, while also addressing the obstacles to fulfilling these rights due to financial constraints. The research concludes with recommendations for strengthening health financing policies, improving governance, and ensuring equitable resource allocation to achieve universal health coverage and protect vulnerable populations.